Exhaled nitric oxide does not provide a marker of vascular endothelial function in healthy humans - Sartori, Claudio; Lepori, Mattia; Busch, Thilo; Duplain, Hervé; Hildebrandt, Wulf; Bärtsch, Peter; Nicod, Pascal; Falke, Konrad J.; Scherrer, Urs (American journal of respiratory and critical care medicine, 1999)
In the lung, nitric oxide synthase (NOS) has been found in both alveolar epithelial and vascular endothelial cells. Nitric oxide (NO) in the exhaled air stemming from the lower respiratory tract has been claimed to represent a marker of the vascular endothelial NO production. Experimental evidence for this concept, however, is lacking. We compared, in eight healthy volunteers, effects on exhaled NO of epithelial NOS inhibition by N G-monomethyl-l-arginine (l-NMMA) inhalation (6 mg/kg over 15 min) with those of endothelial NOS inhibition by l-NMMA infusion (25 μ g/kg/min for 30 min). We also measured blood pressure, heart rate, and l-NMMA plasma concentration. The major new findings were that l-NMMA inhalation which did not have any detectable effect on hemodynamics and l-NMMA plasma concentration, decreased the pulmonary exhaled NO by almost 40%. In contrast, l-NMMA infusion that inhibited endothelial NOS, as evidenced by an increase in blood pressure and a decrease in heart rate, had only a barely detectable effect on exhaled NO ( − 11 ± 4% from baseline). Pulmonary exhaled NO is mostly of epithelial rather than endothelial origin, and does not provide a marker for vascular endothelial NO production and/or endothelial function in healthy humans.
Presented in part at the International Conference of the American Thoracic Soci-ety, Chicago, April 25–29, 1998
Gesehen am 27.08.2019